Media Sosial, Citra Merek, dan Gaya Hidup: Faktor Penentu Keputusan Pembelian Tas Lokal Generasi Z di Tangerang - Siti Asriah Immawati; Aura Nafsa Abidin; Cahyani Kurniastuti (Jurnal Riset Manajemen dan Akuntansi, 2026)
The rapid proliferation of social media has significantly influenced consumption preferences, particularly among Generation Z, a cohort that is highly connected to digital platforms. This phenomenon is particularly relevant for local products, including bags, which are increasingly competing within the digital marketplace. In response to this intensifying competition, local bag manufacturers and marketers are required to establish a strong brand image that resonates with the lifestyle of younger consumers in order to effectively influence their purchasing decisions. Accordingly, this study aims to examine the influence of social media, brand image, and lifestyle on the purchasing decisions of local bags among Generation Z consumers in Tangerang City. A quantitative approach was employed using a survey method involving 250 Generation Z respondents who had previously purchased or used locally produced bags. Data were collected through a structured questionnaire designed to capture demographic characteristics and consumer behaviour. The collected data were subsequently analysed using descriptive statistical techniques to systematically map purchasing behaviour patterns and respondent profiles. The findings indicate that social media serves as the primary source of product-related information, with Instagram emerging as the most dominant platform. Furthermore, brand image and the alignment of products with the lifestyle of Generation Z were found to play a significant role in shaping consumer preferences and purchasing decisions. These results highlight that purchasing decisions are not solely influenced by the functional attributes of a product but are also shaped by self-identity representation and prevailing trends communicated through social media. Therefore, effective marketing strategies should integrate product attributes, brand image, and digital communication that aligns with the lifestyle characteristics of the target consumer segment.